Pengembangan Media Video Pembelajaran Bangun Ruang untuk Pembelajaran Daring Matematika Kelas V Sekolah Dasar - Zeidenes Zenizela; Dwi Kameluh Agustina (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2022)
This research was motivated by the Covid-19 pandemic, the lack of teacher creativity in distance/online learning, the difficulty of students understanding the mathematics of spatial construction. The objectives of this study are (1) to determine the feasibility of online learning video media to build space (2) to determine the level of readability and the response of teachers and students to the use of online learning video media to build space. The research design used was research and development (RnD). Researchers used a development model that was adapted from the 4-D model which is a learning device development model. This model was developed by S. Thiagarajan, Semmel and Semmel (1974). The samples of this research were elementary school teachers for class V and also students for class VI who were in three schools in Blitar Regency. Data collection techniques used expert validation sheets, readability questionnaires and teacher and student responses. The development of this online learning video media uses the Adobe Flash Professional CS6 application. Feasibility test results from media expert validators 89.28% very valid category, material expert 91.21% very valid category, validation of linguists 90.42% very valid category. The results of the teacher's readability test were 97.73% with a very decent category, the results of the students' readability test were 95.71% with a very decent category. The results of the teacher's response test are 94.06% with a very decent category, the results of the student response test are 92.85% with a very decent category.